Anatomical insights into posterior wall isolation in patients with atrial fibrillation: A hypothesis to protect the esophagus. (4th January 2021) - Lu, Xiaofeng; Peng, Shi; Wu, Xiaoyu; Zhou, Genqing; Wei, Yong; Cai, Lidong; Xu, Juan; Ding, Yu; Chen, Songwen; Liu, Shaowen
Abstract: Introduction: Left atrial posterior wall (LAPW) isolation may be performed as an additional atrial fibrillation (AF) ablation strategy based on pulmonary vein isolation. A modified posterior‐inferior line (MPL) was proposed for reducing esophageal injury. The aim of this study was to evaluate the anatomical characteristics of the MPL, compared with the conventional posterior line (CPL). Methods and Results: Multidetector computed tomography was performed in 102 consecutive AF patients (male/female = 60/42) preoperative, and the parameters were evaluated as follows: the distance from MPL and CPL to the esophagus, fat pad presence and thickness in the course of MPL and CPL, and the esophageal route below CPL. The average distance from the MPL to the esophagus was longer than from CPL to the esophagus (3.7 ± 1.5 vs. 1.7 ± 0.4 mm, p < .001). Proportion of fat pad was higher in the course of MPL than CPL. The myocardium tissue and fat pad under MPL was thicker than under CPL (2.9 ± 1.1 vs. 1.6 ± 0.3 mm, p < .001; 1.4 ± 0.6 vs. 0.9 ± 0.2 mm, p < .001), respectively. In patients whose esophagus was unconfined in a triangular space at the left inferior pulmonary vein level, the average distance from MPL to esophagus was longer than the confined patients (4.0 ± 1.7 vs. 3.2 ± 1.0 mm, p = .001). Conclusion: The MPL was far away from the esophagus with thicker myocardium tissue and more fat pad than the CPL; thus, MPL could serve as a favorable alternative in linear ablation for LAPW isolation.